The alamar blue assay in the context of safety testing of nanomaterials - Longhin, Eleonora Marta; El Yamani, Naouale; Rundén-Pran, Elise; Dusinska, Maria (Frontiers in Toxicology, 2022)
The Alamar Blue (AB) assay is widely used to investigate cytotoxicity, cell proliferation and cellular metabolic activity within different fields of toxicology. The use of the assay with nanomaterials (NMs) entails specific aspects that are here addressed by drawing relevant considerations, discussing possible challenges such as interference of the NMs with the test. The procedure of the AB assay applied for testing NMs is described in detail and step-by-step, from the NM preparation, the cell exposure, the inclusion of interference controls, to the analysis and interpretation of the results. Provided that the proper procedure is followed, and relevant controls are included, the AB assay is a reliable and high throughput test to evaluate the cytotoxicity/proliferation/metabolic response of cells exposed to NMs.